Pengembangan Sistem Pendukung Keputusan Berbasis e-Health untuk Skrining Risiko Diabetes Tipe 2 - Demiawan Rachmatta Putro Mudiono; Mudafiq Riyan Pratama; Gamasiano Alfiansyah; Selvia Juwita Swari (BIOS : Jurnal Teknologi Informasi dan Rekayasa Komputer, 2026)
Type 2 diabetes mellitus is a growing global health problem that requires effective early screening strategies. This study aimed to develop an e-Health-based Clinical Decision Support System (CDSS) for assessing type 2 diabetes risk using a rule-based scoring method. The system was developed using a prototype-based system development approach, involving requirement analysis, system design, prototype development, and system evaluation. Risk determination was performed using six major factors including age, sex, body mass index, family history of diabetes, hypertension, and history of gestational diabetes based on ADA and PERKENI guidelines. System evaluation was conducted using black box testing to assess functional performance and usability evaluation using System Usability Scale (SUS) involving end users. The developed system successfully generated risk scores, categorized risk levels, and provided follow-up recommendations aligned with clinical guidelines. Evaluation results indicated that the system functions properly and demonstrates good usability performance. Therefore, the proposed CDSS shows potential as a practical e-Health screening tool to support early diabetes detection in primary healthcare settings.